A comparative analysis of the Australian and New Zealand liquidation schemes. Issue 1 (5th April 2023) - Taylor, Lynne
Abstract: On September 28, 2022, Australia announced an inquiry into the effectiveness of its corporate insolvency laws. The Australia and New Zealand corporate insolvency frameworks have similar objectives and operate in a similar context where, as is the case the world over, most companies are small to medium enterprises. Despite liquidation being just one of several collective and formal corporate insolvency procedures, it is the most frequently occurring procedure in both countries by a large margin. The Australian and New Zealand liquidation schemes have many similarities but also some key differences. Differences include the structure of the respective schemes; the levers prompting liquidation of companies in appropriate circumstances; the role of creditors, the court and the regulator; and the management of low‐value and assetless liquidations. These differences are analysed to determine what, if anything, the New Zealand scheme might contribute to development and/or reform of Australian corporate insolvency law. As consistency and coordination with Australian insolvency law is a New Zealand policy aim, the lessons the Australian scheme might have for New Zealand are also considered. Many of the points on which the Australian and New Zealand liquidation schemes differ are of universal concern (such as the management of low‐value liquidations), meaning that the nature and success (or otherwise) of the Australian and New Zealand responses are of wider, comparative interest.